Exploring the Intentions of White Pepper Farmers in Implementing Agroforestry: A Theory of Planned Behavior Approach in Central Bangka Regency - Pranoto, Yudi Sapta; Justitia, Annisa Ambar; Sitorus, Rostiar (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 19 No 2 (2025): Vol 19 No 2 (2025)DO - 10.24843/SOCA.2025.v19.i02.p02, 2025)
Agroforestry is a sustainable land-use approach that offers both ecological and economic benefits, including for strategic commodities such as Muntok White Pepper in Central Bangka Regency. However, the adoption rate of agroforestry among pepper farmers remains suboptimal, partly due to psychological factors. This study aims to analyze the psychological determinants of farmers' intentions to implement agroforestry using the Theory of Planned Behavior (TPB) framework, which includes three main constructs: attitude toward behavior, subjective norms, and perceived behavioral control. The study was conducted with an explanatory quantitative approach to 105 purposively selected white pepper farmers in Namang and Simpang Katis Districts. Data were collected through a structured questionnaire and analysed using multiple linear regression. The results of the analysis showed that attitudes towards behaviour and perception of behaviour control had a significant effect on farmers' intention to adopt agroforestry, while subjective norms did not have a significant effect. Attitude emerged as the most dominant predictor, highlighting the importance of farmers’ positive perceptions of agroforestry’s benefits. These findings strengthen the applicability of TPB in agroforestry adoption research and provide policy implications for developing behavior-based extension strategies. Policy recommendations should focus on strengthening farmers’ capacity and perceived ability rather than social pressure to enhance agroforestry implementation in white pepper farming systems.